Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/micc.12513
|View full text |Cite
|
Sign up to set email alerts
|

Impaired microvascular reactivity in gestational diabetes is associated with altered glycemic parameters

Abstract: Objectives To assess microvascular reactivity and glycemic parameters in GDM compared to age and GA matched controls. Methods This study involved 21 GDM patients and 31 controls. Microvascular reactivity was assessed using LDF and PORH. Microvascular parameters; PORHmax, PORHpeak, and time to peak perfusion (Tp) were recorded after the release of 3 minutes’ upper arm occlusion. HOMA‐IR was performed to evaluate insulin resistance. Results Average age and GA for subjects were 32.9 years and 29.2 weeks. Mean FBG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…AGEs can also promote insulin resistance and hence trigger diabetes by depleting the antioxidant defenses such as AGE receptor-1 and a survival factor sirtuin-1 [8]. AGEs can undergo post-translational modification of insulin molecule and impair its function [60,61]. Tan et al reported that serum level of AGEs is linked with insulin resistance even in non-obese and non-diabetic subjects, reinforcing the notion that AGEs can be an independent determinant of HOMA-IR [62].…”
Section: Plos Onementioning
confidence: 99%
“…AGEs can also promote insulin resistance and hence trigger diabetes by depleting the antioxidant defenses such as AGE receptor-1 and a survival factor sirtuin-1 [8]. AGEs can undergo post-translational modification of insulin molecule and impair its function [60,61]. Tan et al reported that serum level of AGEs is linked with insulin resistance even in non-obese and non-diabetic subjects, reinforcing the notion that AGEs can be an independent determinant of HOMA-IR [62].…”
Section: Plos Onementioning
confidence: 99%